Mechanical and durability properties of high volume fly ash (HVFA) concrete containing calcium carbonate (CaCO3) nanoparticles - Shaikh, Faiz; Supit, S. (Elsevier BV, 2014)
The effects of CaCO3 nanoparticles on compressive strength and durability properties of high volume fly ash (HVFA) concretes containing 40% and 60% fly ash as partial replacement of cement are evaluated in this study. The experiment is completed in two phases. In the first phase, effects of different nano-CaCO3contents ranged between 1% and 4% on the compressive strength of mortar and concrete are evaluated. The optimum nano-CaCO3 content that exhibited the highest compressive strength is selected to include in high volume fly ash concretes and mortars to evaluate its effects on both early age and later age compressive strengths. The second phase was designed to study the effect of optimum nano-CaCO3 (i.e. 1%)content obtained in the first phase on water sorptivity, volume of permeable voids, chloride permeability, porosity and chloride diffusion of HVFA concretes containing 39% and 59% fly ash and cured at both 28and 90 days. Results show that 1% CaCO3 nanoparticles exhibited the highest compressive strength among all nano-CaCO3 contents and about 22% higher than that of cement mortar. The results also showed that, the HVFA concretes containing 1% CaCO3 nanoparticles have reasonably higher compressive strength, lower volume of permeable voids, porosity, higher resistance to water sorptivity, chloride permeability and chloride ion diffusivity than the counterpart HVFA concretes. It is also found that 1% CaCO3nanoparticles improves the microstructure by forming additional calcium silicate hydrate gels and decreases the calcium hydroxide and calcium silicates of HVFA concretes. It is also revealed that the addition of CaCO3 nanoparticles not only led to much denser microstructure in HVFA matrix but also changed the formation of hydration products, hence contributed to the improvement of early-age compressive strength and durability properties of HVFA concretes.